Land Market Influence on Reproduction of Family Production Systems in Barriga Negra (Lavalleja, Uruguay) - Benítez, Gustavo; Román, Javier; Neumann, Pedro S. (Agrociencia Uruguay, 2019)
Since 2000 in Uruguay was evidenced a significant dynamism in land market accompanied by the 20 % decrease in total establishments, mainly small-scale. The main objective of the research is to understand how the land market has influenced the configuration of livestock production systems in a traditionally livestock region of the country. The study of market influence as a factor of differentiation of the family production systems in Barriga Negra (Lavalleja, Uruguay) was carried out from the method of Analysis-Diagnosis of Agrarian Systems. A typology of the production systems was constructed and typical cases were selected for the accomplishment of economic studies. The types found were forestry companies, livestock ranches, livestock farmers from simple to extended reproduction, and wage-laborers. The main results showed that the price of land acts as a barrier for producers who do not have a productive scale, according to the model. Some systems that do get an accumulation, however, do so from the lease, and therefore, land prices imply a barrier to the purchase and independence. Thus, forest enterprises capture land, push for price increases and appropriate land rent from the lease of these small units. In this context, without public intervention, it seems unlikely that these units will find access mechanisms to land, to make their systems viable, so they tend to abandon production.